Leishmanicidal activity of alkaloids from Hamelia patens - Suárez, Alírica; Diaz, Beth; Tillett, Stephen; Valdivieso, Elizabeth; Compagnone, Reinaldo (Ciencia, 2011)
The crude ethanolic extract from the leaves of Hamelia patens Jacq. was active in vitro against Leishmania mexicana. Partition of the extract, showed that the activity was confined to the dichloromethane extract. The four alkaloids isolated from this extract: isopteropodine (1), palmirine (2), rumberine (3) and mitrajavine (4) were evaluated in vitro for antileishmanial activity. Palmirine (2), one of the main alkaloids, showed the highest leishmanicidal activity with IC50= 56 ÂµM, the alkaloid mitrajavine (4) and the two flavonoids isolated from the ethyl acetate extract: kaempferol-3-O-rutinoside (5), and (-) epicatechine (6) are reported for the first time in this plant.